2023
DOI: 10.3389/feduc.2023.1153647
|View full text |Cite
|
Sign up to set email alerts
|

The bright and dark side of autonomy: How autonomy support and thwarting relate to student motivation and academic functioning

Abstract: According to Self-Determination Theory, autonomy support is essential in fostering optimal learning, growth, and functioning in students across all levels. In contrast, autonomy thwarting is associated with student malfunctioning. The purpose of the current study was to investigate the relationship between perceptions of autonomy support and thwarting, students’ autonomous and controlled motivations, and aspects of student functioning in a higher education setting. The sample consisted of 414 Norwegian univers… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 126 publications
1
3
0
Order By: Relevance
“…This may be due to the reason that students did the class activity as a part of the course and hence found it an external obligation to do. When students feel bound to do a task, they experience controlled motivation (Johansen et al, 2023;Van Soom & Donche, 2014). This was in line with the previous research on goals and motivation in Western cultures (Guay, 2022;Sheldon et al, 2004;Vansteenkiste et al, 2006).…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…This may be due to the reason that students did the class activity as a part of the course and hence found it an external obligation to do. When students feel bound to do a task, they experience controlled motivation (Johansen et al, 2023;Van Soom & Donche, 2014). This was in line with the previous research on goals and motivation in Western cultures (Guay, 2022;Sheldon et al, 2004;Vansteenkiste et al, 2006).…”
Section: Discussionsupporting
confidence: 88%
“…Intrinsic framing may also result in higher levels of amotivation because the participants were not given a choice of reading or not reading in our study, where choice is an important factor that fosters autonomous motivation (Johansen et al, 2023). They did it as a class task that might have given them pressure and caused amotivation.…”
Section: Discussionmentioning
confidence: 97%
“…In other words, it is possible that because students spend little time with each individual teacher, it is difficult to form meaningful connections [49]. However, research on instructor support in higher education, where students spend even less time with individual instructors than in secondary school, has indicated that autonomy-supportive teachers benefit students' perceived competence, motivation, and academic functioning [50,51]. Further, previous research on upper secondary school samples has shown that relationships with teachers are important for students' mental health [9] and completion of their education [1].…”
Section: The Psychosocial Learning Environmentmentioning
confidence: 99%
“…Gamification can have an important contribution: for example, if a gamified design promotes autonomy support through the possibility of choosing an avatar or a mission, if includes social aspects as chats or teamwork to facilitate relatedness and if give instant feedback for an achievement to foster competence, then the gamified experience will promote the basic psychological needs and students will be more positively motivated [e.g., [53] , [54] ]. To be noted that this approach and the research have demonstrated the importance of autonomy in the motivational process [e.g., [50] , [54] , [55] ].…”
Section: Introductionmentioning
confidence: 99%